Behavior of the Ti-Zr-Ni thin film containing quasicrystalline and approximant phases under radiative-thermal action in transition modes - Malykhin, S.V.; Makhlai, V.A.; Surovitskiy, S.V.; Garkusha, I.E.; Herashchenko, S.S.; Kondratenko, V.V.; Kopylets, I.A.; Zubarev, E.N.; Borisova, S.S.; Fedchenko, A.V. (Вопросы атомной науки и техники, 2020)
X-ray diffraction and SEM microscopy were used to study the structural and phase changes in a thin film obtained by magnetron sputtering of a Ti52Zr30Ni18 target (at.%) on a steel substrate under the radiation-thermal influence of pulsed hydrogen plasma on an QSPA Kh-50 accelerator. A technique has been worked out for the formation of the quasicrystalline and crystal-approximant phases as a result of high-speed quenching using pulsed action with a heat load of 0.6 MJ/m². The changes in the contents of these phases as well as in their structure and substructure parameters were studied during isothermal vacuum annealing at a temperature of 550 ℃ and also as a result of irradiation with 5 plasma pulses in the range of heat load from 0.1 to 0.4 MJ/m². The quasicrystalline phase was found to be resistant to irradiation with hydrogen plasma. Методами рентгенівської дифракції та СЄМ вивчені структурні і фазові зміни в тонкій плівці, отриманої магнетронним розпиленням мішені складу Ti52Zr30Ni18 (ат.%) на підкладці зі сталі, при радіаційнотермічному впливі імпульсної водневої плазми на прискорювачі КСПП Х-50. Відпрацьована методика формування квазікристалічної фази і фази кристала-апроксиманта в результаті швидкісного загартування за допомогою імпульсного впливу з тепловим навантаженням 0,6 MДж/м². Вивчено зміну параметрів структури і субструктури, а також вмісту зазначених фаз при ізотермічному вакуумному відпалі при температурі 550 ℃, а також в результаті опромінення 5 імпульсами плазми в інтервалі теплового навантаження від 0,1 до 0,4 МДж/м². Квазікристалічна фаза виявилася стійкою до опромінення водневою плазмою. Методами рентгеновской дифракции и СЭМ изучены структурные и фазовые изменения в тонкой пленке, полученной магнетронным распылением мишени состава Ti52Zr30Ni18 (ат.%) на подложке из стали, при радиационно-термическом воздействии импульсной водородной плазмы на ускорителе КСПУ Х-50. Отработана методика формирования квазикристаллической фазы и фазы кристалла-аппроксиманта в результате скоростной закалки с помощью импульсного воздействия с тепловой нагрузкой 0,6 MДж/м². Изучены изменение параметров структуры и субструктуры, а также содержания указанных фаз при изотермическом вакуумном отжиге при температуре 550 ℃, а также в результате облучения 5 импульсами плазмы в интервале тепловой нагрузки 0,1…0,4 МДж/м². Квазикристаллическая фаза оказалась устойчивой к облучению водородной плазмой.